2020
DOI: 10.1007/s12140-020-09333-y
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Students Choosing Hungarian Tertiary Education: a Systematic Review

Abstract: China has been the leading source of foreign students pursuing tertiary degrees in other countries. The incoming Chinese students in Hungary comprised the third highest number of foreign students in the country in 2016. This paper examines the Chinese students’ motivations for choosing the Hungarian education system, with the purpose of gaining a more comprehensive and accurate understanding of the flow of Chinese students to Hungary. In terms of methodology, this paper uses the systematic review protocol by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In this study, the participants sought to gain proficiency in the Chinese language and knowledge of Chinese culture so they could engage with professional networks for community work, academic opportunities, and for educational development. A recent study (Li, 2020) found that many Chinese undergraduates, postgraduate students, and researchers have decided to come to Europe to further their education. The findings of this study complement those of previous studies, particularly about the migration of Chinese professionals into global communities, regardless of geographic locations.…”
Section: Friendships Network and Education: Chinese Immigrants And Pr...mentioning
confidence: 99%
“…In this study, the participants sought to gain proficiency in the Chinese language and knowledge of Chinese culture so they could engage with professional networks for community work, academic opportunities, and for educational development. A recent study (Li, 2020) found that many Chinese undergraduates, postgraduate students, and researchers have decided to come to Europe to further their education. The findings of this study complement those of previous studies, particularly about the migration of Chinese professionals into global communities, regardless of geographic locations.…”
Section: Friendships Network and Education: Chinese Immigrants And Pr...mentioning
confidence: 99%
“…Students from the working class are over-represented in lower-prestige courses that predominantly result in unclear professional outcomes (Fehérvári et al, 2016;Nyüsti, 2018). Some of the Chinese students who study in Hungary are regarded as disadvantaged in terms of cultural capital, although there is little literature regarding the situation in Central and Eastern European countries (Li, 2020). Hungary aims to attract more Chinese students and supports around 500 per year with the Stipendium Hungaricum, which attracts international students by implementing multilateral agreements for international students to study in Hungary that cover their tuition fees and funding housing/living costs.…”
Section: The Bologna Process and Educational Mobility With Respect To...mentioning
confidence: 99%
“…In recent years, the interest in exploring the students' motivation for learning Hungarian had grown; several studies have been conducted to explore the motivation that students have to learn Hungarian (Hosseini-Nezhad, Safdar, & Luu, 2019;Khudur, 2019;Xueyan, 2020;Zhang, 2018). This interest may be due to the rise in the number of international students during the last decade.…”
Section: Motivation For Learning Hungarianmentioning
confidence: 99%
“…Csizer and Kalman (2019) pointed out that the learning success combined with the teacher's character, contact experiences, and the attitudes towards the language community as the most influential factors. Xueyan (2020) claimed that the opportunity for language development provided by the state Tempus scholarship foundation (TPF), both for learning English and Hungarian languages plays an essential role in choosing Hungary as international students destination. For instance, Zhang (2018) found that Chinese students have positive attitudes towards learning Hungarian for academic purposes and personal integration in the local community.…”
Section: Motivation For Learning Hungarianmentioning
confidence: 99%